Kebijakan Kawasan Tanpa Rokok dalam Optik Maqosid Syariah di Kota Pekalongan - Anoraga, Muhammad Birawa (Manabia: Journal of Constitutional Law, 2024)
The implementation of smoke-free areas is an effort to protect and guarantee the right of everyone to breathe clean air without cigarette smoke. Pekalongan City Regional Regulation Number 19 of 2012 concerning smoke-free areas regulates areas or rooms that are prohibited for smoking activities. The type of research used is empirical juridical with a qualitative approach, with a maqasid sharia perspective. The results of the study indicate that the implementation of smoke-free areas based on Pekalongan City Regional Regulation Number 19 of 2012 concerning smoke-free areas is running well but not yet optimal. The implementation of this KTR regulation is in accordance with Islamic teachings, namely the importance of maintaining health and avoiding all its harms, this is included in the maqasid sharia. That maintaining the soul in it there is a spirit as a mandate from Allah SWT which is a control of all human beings physically and mentally. This is the reason for how important it is to keep the soul healthy, pure, and functioning properly. At this level it is included in hifz-nafs (protection of the soul).